THE CORELATION BETWEEN COMPLIANCE WITH DRINKING OAT "TUBERCOLOSIS DRUG" AND THE HEALING STATUS OF PULMONARY TB PATIENTS IN THE LUNG CLINIC - Sri Utami; Achmad Dafir Firdaus; Sismala Harningtyas (PROFESSIONAL HEALTH JOURNAL, 2024)
Tuberculosis (TB) is an infectious chronic disease caused by Mycobacterium tuberculosis bacteria that can attack the lungs but can also affect various other organs such as the pleura, lymph nodes, bones, and other extra-pulmonary organs. Adherence to medication is the patient's attitude toward taking medication as recommended. This study used the purposive sampling technique with a retrospective approach; the sample consisted of 40 respondents. Data were collected by looking at medical record data and analyzed using the Chi-Square test. The results showed that of the 40 patients studied, there were 13 who were compliant and 10 who were declared cured. The results of the statistical test analysis obtained a pvalue so is rejected and is accepted. So there is a relationship between adherence to medication and recovery status. There are still many pulmonary TB patients who are not cured because they are not compliant with treatment. Adherence to taking medication is an important indicator of the patient's recovery status, but compliance is influenced by a lack of awareness of the importance of treatment, such as preferring herbal remedies, not wanting to take medicine again because they feel their body is healthy, and not controlling because of long-term out-of-town work. So that strong support is needed both from the family, health workers, and also from pulmonary TB survivors.